ANALISIS PARTISIPASI MASYARAKAT SEBAGAI PENYELENGGARA PEMILU 2024 DI DESA KERTAJAYA KABUPATEN PANGANDARAN - Aziz, Nur (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2024)
The 2024 general election is one of Indonesia's democratic events, allowing people to choose their future leaders. Creating a successful democratic atmosphere relies heavily on community participation in organizing the 2024 election. This study aims to analyze the participation of young people as KPPS in the 2024 general election in Kertajaya Village, Cigugur District, Pangandaran Regency, where youth participation remains low. The study was conducted in Kertajaya Village, Cigugur District, Pangandaran Regency, West Java Province. The research uses a qualitative method with a descriptive approach to provide a systematic, factual, and accurate description of the factors, characteristics, and relationships among the phenomena being investigated. Data was collected through in-depth interviews and literature reviews. Data analysis was conducted using the new institutional approach, political participation theory, the concept of general elections, and the role of youth in general elections to analyze the focus of the study. The study found that in the KPPS recruitment process, the initiative from the community to register independently was very low. The factors that hinder youth participation include a lack of self-confidence, the apathetic attitude of youths who are reluctant to engage in the election process, insufficient information they receive, the attitude of election organizers at the village or sub-district level that does not trust young people, and the requirements that incur additional costs. Thus, the General Election Commission must make maximum efforts to increase youth participation as KPPS in the 2024 general election.